The elegies of Maximianus - Maximianus,Juster, A. M.,Roberts, Michael (PENN - University of Pennsylvania Press, 2018)
Preface – Introduction / by Michael Roberts – Elegies: Elegy 1 – Elegy 2 – Elegy 3 – Elegy 4 – Elegy 5 – Elegy 6 – Appendix A. Cassiodorus, Variae 1.21 – Appendix B. The Appendix Maximiani – Appendix C. De Boetio Spata Cincto – Appendix D. Imitatio Maximiani – Appendix E. Le Regret de Maximian – Notes – Bibliography
Includes bibliographical references (pages 211-223)
Keywords: Kommentar; Maximianus; active 6th century